2013
DOI: 10.1097/mpa.0b013e3182575e4a
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-dioxygenase Affects the Aggressiveness of Intraductal Papillary Mucinous Neoplasms Through Foxp3+CD4+CD25+ T Cells in Peripheral Blood

Abstract: Peripheral Foxp3(+) Tregs accurately reflect the aggressiveness of IPMNs. An increase in Foxp3(+) Tregs can be induced by local IDO-positive cells in IPMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Therefore, we hypothesized a certain molecule which was induced by IFN-γ in non CD4+ cells suppressed the production of IL-17 of CD4+ T cells. IDO was one of the candidate molecules as it was induced by IFN-γ [25] in non CD4+ cells and known to be associated with Treg [26][29] which suppresses Th17. Pretreatment of 1-MT partially restored the production of IL-17 suppressed by IFN-γ (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we hypothesized a certain molecule which was induced by IFN-γ in non CD4+ cells suppressed the production of IL-17 of CD4+ T cells. IDO was one of the candidate molecules as it was induced by IFN-γ [25] in non CD4+ cells and known to be associated with Treg [26][29] which suppresses Th17. Pretreatment of 1-MT partially restored the production of IL-17 suppressed by IFN-γ (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…We previously showed that Foxp3 + Treg populations in peripheral blood can reflect the pathological aggressiveness of pancreatic ductal carcinomas and IPMNs (4,12). The numbers of Foxp3 + T cells were found to be increased in immune cells infiltrating pancreatic cancers and in draining lymph nodes (7,22), however, the mechanism by which Foxp3+Treg populations are expanded in peripheral blood from the tumor environment remained unclear (23).…”
Section: Discussionmentioning
confidence: 99%
“…IDO is a critical enzyme for maintaining pregnancy (9) and plays an important role in tumor immunity (10,11). An investigation of the associations of IDO with IPMN aggressiveness and Treg immunity showed that Treg increases induced by IDO + DCs are associated with peritumoral lesions (12). However, the mechanism underlying the expansion of Tregs in peripheral blood, as well as in the peritumoral environment, remains unclear.…”
mentioning
confidence: 99%
“…IDO-positive cells in IPMNs can induce an increase in the FOXP3+ cells. [51] Natural Killer (NK) cells are key components in the innate immune system and are capable of destroying the cancer cells directly. Dysfunction of NK cells has been investigated in pancreatic cancer.…”
Section: Ido In Prostate Cancermentioning
confidence: 99%
“…IDO is involved in immune system regulation. IDO upregulation is associated with poor prognosis in various cancers [20,30,34,35,39,41,43,51] but few studies suggested that increased expression of IDO was linked with favourable prognosis. [19,46] Further studies are required in view of the contradictory findings, to comprehend this complex role of IDO in various cancers.…”
Section: Ido As An Immunotherapeutic Targetmentioning
confidence: 99%